A holistic carrier-bound immobilization approach for unspecific peroxygenase - De Santis, Piera; Petrovai, Noémi; Meyer, Lars-Erik; Hobisch, Markus; Kara, Selin (Frontiers in Chemistry, 2022)
Unspecific peroxygenases (UPOs) are among the most studied enzymes in the last decade and their well-deserved fame owes to the enzyme’s ability of catalyzing the regio- and stereospecific hydroxylation of non-activated C–H bonds at the only expense of H2O2. This leads to more direct routes for the synthesis of different chiral compounds as well as to easier oxyfunctionalization of complex molecules. Unfortunately, due to the high sensitivity towards the process conditions, UPOs’ application at industrial level has been hampered until now. However, this challenge can be overcome by enzyme immobilization, a valid strategy that has been proven to give several benefits. Within this article, we present three different immobilization procedures suitable for UPOs and two of them led to very promising results. The immobilized enzyme, indeed, shows longer stability and increased robustness to reaction conditions. The immobilized enzyme half-life time is 15-fold higher than for the free AaeUPO PaDa-I and no enzyme deactivation occurred when incubated in organic media for 120 h. Moreover, AaeUPO PaDa-I is proved to be recycled and reused up to 7 times when immobilized.